Day‐to‐day variation in students' academic success: The role of self‐regulation, working memory, and achievement goals. Issue 6 (15th July 2022) - Blume, Friederike; Irmer, Andrea; Dirk, Judith; Schmiedek, Florian
Abstract: Self‐regulation was found to be positively associated with school performance. Interrelations between self‐regulation, working memory (WM), and achievement goals, in particular mastery goals, have been established, as well as associations with academic outcomes. It stands to reason that self‐regulation, WM, achievement goals, and academic success are related on a daily level. However, previous research rarely considered this level of analysis. Here, we therefore addressed the relations of daily self‐regulation, WM, and achievement goals, and their relevance for daily and general academic success. Data were obtained through ambulatory assessments in 90 students before (Study 1; Mage  = 9.83, SDage  = 0.50) and 108 students after their transition to secondary school (Study 2; Mage  =  10.12, SDage  = 0.45) across 20 school days. Students reported about daily achievement goals prior to school, self‐regulation at school, and perceived academic success after school, as well as report card grades. Daily WM was assessed at school. Study 1 showed positive associations between daily mastery goals and self‐regulation, but not with WM. Together, daily performance‐approach goals and self‐regulation, but not other goals or WM uniquely contributed to daily perceived academic success. Study 2 showed positive associations between daily mastery goals and self‐regulation, but not with WM. Average daily mastery goals predicted daily WM. Together, daily mastery goals and self‐regulation, but not WM, uniquely contributed to daily perceived academic success. In both studies, average levels of WM, but not achievement goals or self‐regulation predicted report card grades. Results thus corroborate theoretical considerations on the importance of distinguishing self‐regulation processes at between‐ and within‐person levels. Research Highlights: Analyses of intensive longitudinal data on daily self‐regulation, working memory, and achievement goal orientations in the school context of 9‐ to 11‐year‐olds. In primary and secondary school, days with higher mastery goals and self‐regulation are days with higher academic success. In primary and secondary school, days with higher mastery goals are days with higher self‐regulation. In secondary school, students with higher average mastery goals show better daily WM performance. Average working memory performance predicts report card grades beyond the influence of prior grades and achievement goal orientations. Abstract : Intensive longitudinal data collected from 90 students right before (Study 1) and 108 students right after their transition to secondary school (Study 2) showed positive associations between daily mastery goals and self‐regulation, but not with WM, in both samples. In Study 1, together, daily performance‐approach goals and self‐regulation, but not other goals or WM, and in Study 2, together, daily mastery goals and self‐regulation, but not other goals or WM, uniquely contributed to daily perceived academic success. Contrasting previous findings from studies considering the between‐person level only, the results thus corroborate theoretical considerations on the importance of distinguishing self‐regulation processes at between‐ and within‐person levels.